Determinants of short birth interval among married multiparous women in Chinaksen district, eastern Ethiopia: a case-control study - Aleye, Bekry; Usso, Ahmedin Aliyi; Mengistie, Bezatu; Dessie, Yadeta; Adem, Hassen Abdi; Alemu, Addisu; Yuya, Mohammed; Mohammed, Aminu (Frontiers in Global Women's Health, 2024)
Background The short birth interval is a common public health issue that affects women's and children's health in sub-Saharan Africa. Despite a higher burden of short birth intervals reported in Ethiopia, there is limited evidence to indicate the primary risk factors, particularly in rural eastern Ethiopia. Therefore, this study assessed the determinants of the short birth interval among married multiparous women in Chinaksen district, Eastern Ethiopia. Methods A community-based case-control study was conducted among randomly selected 210 cases and 210 controls from April 01 to June 30, 2019. The total sample size (219 cases and 219 controls) were calculated using Epi-Info software version 7.2. Data were entered using EpiData version 3.1 and analyzed using SPSS version 27, and multivariable logistic regression analyses conducted to identify the determinants of short birth intervals. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to report the strength of association and statistical significance declared at p-value < 0.05. Results The women in the young age group (AOR = 2.33, 95% CI: 1.03, 5.26), missed their antenatal care visits (AOR = 2.23, 95% CI: 1.18, 4.21), failed to utilize postpartum contraceptives (AOR = 5.98, 95% CI: 3.62, 9.89), did not attend postnatal care visit (AOR = 1.86, 95% CI: 1.13, 3.05), nonexclusive breastfed (AOR = 4.05, 95% CI: 2.18, 7.52), short and medium period of breastfeeding (AOR = 4.00, 95% CI: 1.34, 12.10) and (AOR = 3.56, 95% CI: 1.62, 7.82), respectively and female sex of preceding child (AOR = 1.92, 95% CI: 1.18, 3.12) were the important risk factors of short birth interval. Conclusions Women's age, antenatal care visits, postnatal care attendance, utilization of postpartum contraceptives, exclusive breastfeeding practice, duration of breastfeeding, and sex of the preceding child were the primary predictors of short birth intervals. Improving the utilization of maternal healthcare services in health facilities would be imperative to prevent and reduce short birth intervals, and its negative consequences.